Precision medicine and improving the outcomes of atrial tachycardia ablation: a comprehensive review - Mikołaj Młyński; Grzegorz Sławiński; Dariusz Kozłowski (European Journal of Translational and Clinical Medicine, 2024)
Atrial tachycardia (AT) is a prevalent cardiac arrhythmia characterized by rapid, abnormal electrical activity originating from the atria. It represents a significant clinical challenge due to its potential for recurrence, adverse cardiovascular outcomes and impact on quality of life. Catheter ablation has emerged as a primary therapeutic modality for AT, offering the potential for rhythm control and symptom alleviation. Despite advancements in techniques and technology, the success of AT ablation can vary widely among patients. Identifying prognostic factors associated with successful AT ablation and potential outcome improving techniques is imperative for optimizing patient care.